2015
DOI: 10.1515/revneuro-2014-0067
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll-like receptor/MYD88 signaling in neurodegenerative diseases

Abstract: AbstractToll-like receptors (TLRs) are important innate immune proteins, and the activation of the TLRs results in the activation of intracellular signaling pathways, leading to the expression of proinflammatory cytokines that are essential to the identification and clearance of invading pathogens. TLR signaling occurs through adaptor proteins, most commonly myeloid differentiation primary response gene 88 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 70 publications
1
27
0
2
Order By: Relevance
“…Indeed, we also found that TLR2 and TLR4 were expressed on RBA-1 cells. A previous study has shown that TLR-mediated signalings play a critical role in neurodegenerative diseases, such as Alzheimer s disease, Parkinson s disease, amyotrophic lateral sclerosis, and multiple system atrophy [37]. Here, we proved that LPS potentially enhanced MMP-9 expression and cell migration, mainly via TLR4 activation, as transfection with TLR4 but not TLR2 siRNA attenuated the LPS-mediated responses and phosphorylation of downstream signaling molecules.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, we also found that TLR2 and TLR4 were expressed on RBA-1 cells. A previous study has shown that TLR-mediated signalings play a critical role in neurodegenerative diseases, such as Alzheimer s disease, Parkinson s disease, amyotrophic lateral sclerosis, and multiple system atrophy [37]. Here, we proved that LPS potentially enhanced MMP-9 expression and cell migration, mainly via TLR4 activation, as transfection with TLR4 but not TLR2 siRNA attenuated the LPS-mediated responses and phosphorylation of downstream signaling molecules.…”
Section: Discussionsupporting
confidence: 53%
“…When TLRs recognize PAMPs or DAMPs, the DD of MyD88 interacts with the DD of IL-1 receptor-associated kinase-4 (IRAK-4) and forms the MyD88-IRAK-4 complex, which recruits IRAK-1 and IRAK-2, resulting in the phosphorylation of IRAKs. IRAKs leave MyD88 after phosphorylation and interact with tumor necrosis factor receptor-associated factor 6 (TRAF6; Xiang et al, 2015). TRAF6 then induces the activation of TGFβ activated kinase-1 (TAK-1) and TAK1-binding proteins (TAB) 2 and 3, which consequently activate the nuclear factor-κB (NF-κB) signaling pathway by phosphorylating I-κB (IκB).…”
Section: Structures and Biological Functions Of Tlrs And Myd88mentioning
confidence: 99%
“…Additionally, TAK-1 can also activate c-Jun N-terminal kinase (JNK), mitogen-activated protein kinase (MAPK) and Phosphatidylinositol 3-Kinases (PI3K). The activation of these downstream kinases and pathways leads to a cascade of inflammatory responses (Xiang et al, 2015).…”
Section: Structures and Biological Functions Of Tlrs And Myd88mentioning
confidence: 99%
“…In particular, TRL4, a member of the TRLs family that has been involved in neuroinflammatory diseases [41], is expressed on microglia and it is activated in response to different stimuli/injury. The TRL4 stimulation triggers the activation of signaling cascades which generally culminate in the expression of the Nuclear Factor-kappa B (NF-κB) [42] and the NF-κB-mediated transcription of pro-inflammatory genes [43,44,45]. The prolonged release of proinflammatory mediators such as cytokines (IL-1β, IL-6, TNF-α, IL-8, TGF-β), chemokines, prostaglandins, inducible nitric oxide synthase, cyclooxygenase-2 and free radicals by microglia, leads to chronic inflammation and stimulates the adaptive immune response, mediated by peripheral T-cells and macrophages that are recruited in the CNS.…”
Section: The Wnt Canonical Signaling In Neuroinflammationmentioning
confidence: 99%